The idea of the polyfunctional essence of art as a problem of modern aesthetics - G.G. Kolomiets; Ya.V. Parusimova (Интеллект. Инновации. Инвестиции, 2021)
The appeal to the problem of polyfunctionality of art is caused by the modern post-postmodern situation in the field of philosophical and cultural knowledge, which raised the problem of understanding the essence of art and its existence. A stochastic state was revealed, an uncertainty in view of the transformations of art itself, following not only the footsteps of the changing world, but also anticipating civilizational shifts, guessing a lot of probabilities and possibilities in the cultural movement of humanity. In this regard, the article rethinks the problem of the polyfunctionality of art and puts forward the idea of the polyfunctionality of art in the problematic field of aesthetics. Art is considered by the authors from the point of view of phenomenology and axiology as an aesthetic way of being in the human world, as a valuable interaction of a person with the world, as a subject of constructing new meanings and meanings by the consciousness when meeting with art. The article asserts the polyfunctional essence of art, which, according to the authors, stems from the variety of interpretations of the concept of «art» in the history of aesthetic thought and modern discourse, due to the multidimensional nature of its manifestations in the human life world. After analyzing various approaches to the understanding of art, and following the phenomenological methodology, as well as the ontological method and axiological approach, the authors came to the conclusion that definitions do not answer the question «what is art?», they rather say «what is art for?». In other words, it is not «what is» that is defined, but «what it means». It is noted that the leading functions recognized in aesthetics, such as aesthetic, communicative, harmonizing, transforming, are predominant at certain stages of culture, but they are separate functions of art that do not exhaust the fullness of the multifunctional essence, the ideological integrity of art in culture. It is pointed out that at the present stage, the features of openness, isolation, and «atomicity» of the communicative discourse are becoming more and more acute, leading to a change in the models of art functions, determining the problematic nature of the aesthetic «super-function» of art in the promotion of civilizational and cultural space. The idea of the polyfunctional essence of art presupposes a specific form of mental development of the polyfunctionality of art, is the principle of explaining the existence of art and includes the process of further searching for the definition of art on the basis of its multi-valued existence in culture.